2012
DOI: 10.5414/cn107398
|View full text |Cite
|
Sign up to set email alerts
|

Vascular stiffness in incident peritoneal dialysis patients over time

Abstract: In this group of incident PD patients, we demonstrate a lower prevalence of vascular calcification than in hemodialysis patients, a correlation of calcification with PWV, and an important finding that PWV can change in either direction over a short period of time, which are associated with modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Notably, we did not see any correlation between changes in baPWV and HbA1c or body-fluid overload (ΔECW/ TBW) during PD, consistent with the observations by others. [18][19][20][21] Moreover, there was no relationship between changes in baPWV and serum calcium and phosphorus levels. These results together suggested that BP control is the first-line approach to retard or even reverse vascular stiffness in the first few years after introducing PD.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Notably, we did not see any correlation between changes in baPWV and HbA1c or body-fluid overload (ΔECW/ TBW) during PD, consistent with the observations by others. [18][19][20][21] Moreover, there was no relationship between changes in baPWV and serum calcium and phosphorus levels. These results together suggested that BP control is the first-line approach to retard or even reverse vascular stiffness in the first few years after introducing PD.…”
Section: Discussionmentioning
confidence: 87%
“…11,13) Most previous studies employed the femoral and heart (hfPWV) 18) or carotid (cfPWV), a well-established index of central arterial stiffness. [19][20][21] The cfPWV measures stiffness from the aorta to iliofemoral axes, while baPWV reflects one in not only central elastic arteries but also peripheral muscular arteries. Our 2-year follow-up observations indicated that BP is a prime determinant of baPWV: nearly half of our patients had a decreasing baPWV during the first PD year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase was also observed in carotid-radial PWV. In contrast, Tang and coworkers showed that a PWV improvement found in peritoneal dialysis patients is associated with modifiable risk factors [ 18 ]. The authors found that 23% of patients undergo a decrease of carotid-femoral PWV values after a six-month follow-up, compared to the baseline data ( Table 2 ).…”
Section: Peritoneal Dialysis and Arterial Stiffnessmentioning
confidence: 99%
“…Since the aorta is the principal capacitive element of the arterial tree, non-invasive measurements of stiffness in the aorta obtained by applanation tonometry using the carotid-femoral pulse wave velocity (cf-PWV) can more accurately reflect the physiologic effects of increased arterial stiffness on the heart [ 13 , 14 ]. Indeed, elevated cf-PWV in ESRD patients who are treated with peritoneal dialysis, hemodialysis, or renal transplantation is an excellent predictor of fatal cardiovascular events and all-cause mortality [ 15 19 ]. An increase of 1 m/s in cf-PWV in ESRD patients increases both cardiovascular and overall mortality by 34 % by crude estimates and by 14 % after adjusted analyses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%